Effect of Increasing Body Mass Index On the Activity of Matrix Metalloproteinase-2: Life Sciences-Biochemistry - Jain, Richa; Das, Biswajit; Saxena, Shikha; Gupta, Gaurav (International Journal of Life Science and Pharma Research, 2022)
The Increasing Body Mass Index is one of the major concerns in today’s lifestyle, which may give rise to various disorders. Studies have suggested that Matrix Metalloproteinases (MMPs) are associated with Obesity and cardiovascular disease. This study aimed to evaluate the serum activity of Matrix Metalloproteinase-2 in overweight patients with anthropometric measurements to assess the effect of body mass index in MMP-2 activity. In this Age and sex matched case-control study the participants were selected in 2:1 ratio (219 cases and 108 controls). In this study Body Mass Index, Blood Pressure, and other biochemical parameters i.e. Fasting Blood Sugar (FBS), Total Cholesterol (TC), Triglycerides (TG), High-density lipoprotein cholesterol (HDL-C), Low-density lipoprotein cholesterol (LDL-C) along with MMP-2 were measured through semi-autoanalyzer and ELISA respectively. There was an increased concentration of FBS in overweight patients compared to the control group, which was statistically significant. In the case of lipid profile, there was an elevated concentration of TC, TG, and LDLC in the overweight population when compared to the control group and the findings were statistically significant, while HDL-C was significantly elevated in the control group compared to the case group. With respect to blood pressure, a significant increase was observed in systolic and diastolic blood pressure. In this study, there was a significant elevation of MMP-2 in the case group compared to the control group, which was positively associated with Body Mass Index. The outcome of this study revealed that increasing body weight might be the root cause of developing several life-threatening risk factors if not considered at initial level. Furthermore, altered concentration of MMP-2 in overweight patients may highlight cardiovascular Risk in these patients.